Effect of yttrium content on microstructure and tensile properties of as-cast and as-solutionized Al-Zn-Mg-Cu alloys - Mojia Li; Yingbo Zhang; Yunfeng Hu; Jiaheng Li; Qi Zeng; Pu Zhang (Materials Research Express, 2023)
Four kinds of 7xxx series aluminum alloys with different Y elementcontents were obtained by ordinary gravity casting. The effect of Y content on the microstructure and mechanical properties of as-cast and as-solutionized Al-7.9Zn-3Mg-2.4Cu-0.13Zr (wt%) alloys were investigated by means of x-ray diffraction (XRD), electron backscattering diffraction (EBSD), scanning electron microscopy (SEM), energy dispersive spectrometer (EDS) and room-temperature tensile tests. The results shows that, in as-cast condition, Y element can refine the grain and reduce the content of Mg(Zn, Cu, Al) _2 lamellar phases at the interdendritic. (Al, Zn) _8 Cu _4 Y block-shaped phases form in interdendritic regions. After solution treatment, the undissolved Mg(Zn, Cu, Al) _2 phases evolved from lamellar to bulk-like which distribution in interdendritic, but no obvious change in (Al, Zn) _8 Cu _4 Y phase. The tensile testing results shows that the optimal yttrium content is 0.45 wt%. At 0.45 wt% Y, the ultimate tensile strength and elongation are 267 MPa and 2.4% in as-cast condition and 420 MPa and 3.6% in as-solutionized condition.